Family system and deprivation of liberty : narratives about the past, present and future - Politti, Mariana (2023)
Fil: Politti, M. Pontificia Universidad Católica Argentina. Facultad de Psicología y Psicopedagogía. Centro de Investigaciones en Psicología y Psicopedagogía; Argentina